Surgical treatment of scoliosis using Harrington instrumentation and arthrodesis. A comparison of 2 series with and without sublaminar segmental wiring - Daruwalla, J.S. (2013)
Revue de Chirurgie Orthopedique et Reparatrice de l'Appareil Moteur